THE REQUEST STRATEGY OF SUMATRAN INFORMANTS IN PERFORMING SPEECH ACTS REQUEST - Yulita, Delti; Siahaan, Desta Gloria (English Study Program, Faculty of Teacher Training and Educational Sciences, Universitas Timor, 2021)
This present study was proposed to investigate the notion of request speech acts among native Sumatran. The informants took a Discourse Completion Test (DCT) consists of eight scenarios and respond it based on the situation given. The responses were analyzed by directness categories in scale designed by Blum-Kulka et al (1984) named Cross-Cultural Study of Speech Act Realization Patterns (CCSARP). The result shows that Sumatran informants mostly use conventionally indirect request as a strategy in formulating request speech acts. The outcomes revealed that a high number of politeness marker is employed along with grounded as parts of external and internal modification in request performing.